A new terrestrial talitrid genus from the Philippine Islands (Crustacea, Amphipoda, Talitrida, Talitridae) and the designation of two informal subgroups - Lowry, James K.; Coleman, Charles Oliver (Zootaxa, 2012)
Curiotalitrus, a new genus of terrestrial land-hoppers (Amphipoda, Talitridae) is described from rain-forests in the Phil-ippines. Curiotalitrus includes one species: C. curioi (Javier & Coleman, 2010). Informal Talitrus and Orchestia groups are proposed based on the condition of the male second gnathopod.